2001
DOI: 10.1007/s00464-001-8306-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gallstone disease in the laparoscopic era

Abstract: Body mass index, breast-feeding, oral contraceptives, parity > 2, and family history were found to be risk factors for gallstone disease. Age and female sex were not, probably due to selection bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
10
1
2
Order By: Relevance
“…However, because of the 1982 national policy of family planning in China, women were allowed to give birth to only one child and underwent tubal ligation after their first delivery. This led to a reduction in risk factors for gallstone formation, such as being biologically reproductive and taking oral contraceptives . A large number of clinical research in Beijing suggested that the levels of cholesterol in men were higher than those in women .…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the 1982 national policy of family planning in China, women were allowed to give birth to only one child and underwent tubal ligation after their first delivery. This led to a reduction in risk factors for gallstone formation, such as being biologically reproductive and taking oral contraceptives . A large number of clinical research in Beijing suggested that the levels of cholesterol in men were higher than those in women .…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors associated with GSD are age, race, sex, family history of GSD, obesity, rapid weight loss, number of children, and use of oral contraceptives or estrogen replacement therapy. 4 In a study of gallstones in a Danish population, it was reported that BMI and slimming treatments were significantly associated with GSD. 5 In Taiwan, age over 60 years and diabetes mellitus were risk factors for GSD among older persons.…”
Section: Introductionmentioning
confidence: 99%
“…The data from academic literature represent a problem of not paying attention to serious pathologies during an operation, including malignant neoplasm of the digestive track, accompanying gall-stones (2-9). The key role plays gastroduodenoscopy (10)(11)(12)(13)(14). In Poland there is no established standard, as for gastroscopy being performed in a routine way before an operation of removing a gall-bladder.…”
mentioning
confidence: 99%